The Four Core Genotypes mouse model: evaluating the impact of a recently discovered translocation - Carrie B. Wiese; Barbara Soliman; Karen Reue (Biology of Sex Differences)
Abstract The Four Core Genotypes (FCG) mouse model has become a valuable model to study the mechanistic basis for biological sex differences. This model allows discrimination between influences of gonadal sex (ovaries or testes) from those associated with genetic sex (presence of XX or XY chromosome complement). FCG mice have illuminated distinct effects of gonadal and chromosomal sex on traits ranging from brain structure and behavior to vulnerability to obesity, atherosclerosis, multiple sclerosis, Alzheimer’s and other diseases. A recent study determined that the Y Sry− chromosome used in a specific line of C57BL/6J FCG mice harbors nine genes that have been duplicated from the X chromosome. This report raised concern that scores of publications that previously used the FCG model may therefore be flawed, but did not provide details regarding how studies can be evaluated for potential impact (or lack of impact) of the translocation. Here we (1) provide a practical description of the genetic translocation for researchers using the FCG model, (2) document that a majority of the studies cited in the recent report are unlikely to be affected by the translocation, (3) provide a scheme for interpreting data from studies with FCG mice harboring the Y Sry− translocation, and (4) delineate expression levels of the nine translocated genes across tissue/cell types as a filter for evaluating their potential involvement in specific phenotypes.